2021
DOI: 10.1111/cts.13218
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the influence of light between circularly polarized and linearly polarized smartphones on dry eye symptoms and asthenopia

Abstract: This paper aims to investigate the efficacy of circularly polarized light smartphones in affecting dry eye symptoms and asthenopia through a comparison with linearly polarized smartphones. One hundred twenty participants were randomly divided into four groups. Dry eye and asthenopia symptoms were evaluated using the Ocular Surface Disease Index (OSDI), Computer Vision Syndrome Scale 17 (CVSS17), Convergence Insufficiency Symptom Survey (CISS), and visual analogue scale (VAS). Objective ocular examinations were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 25 publications
0
15
0
1
Order By: Relevance
“…Moreover, Mou et al 10 revealed that smartphone with circularly polarized light was much better than smartphone with linearly polarized light in terms of alleviating CVS eye strain, DED, and ocular discomfort as circularly polarized light has closer properties of natural light. 10 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, Mou et al 10 revealed that smartphone with circularly polarized light was much better than smartphone with linearly polarized light in terms of alleviating CVS eye strain, DED, and ocular discomfort as circularly polarized light has closer properties of natural light. 10 …”
Section: Discussionmentioning
confidence: 99%
“… 40 Linearly polarized smartphones are responsible for asthenopia and reduced confusion flicker frequency. 10 Smartphone has adverse effects on binocular vision by decreasing the binocular accommodative facility. 44 Electronic devices might be responsible for accommodative disorders and convergence insufficiency in pediatric users.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The research intended to recruit patients in order to have a signi cant clinical difference with a con dence interval of 95 % power (=0.05) based on a previous research sample size calculation n=30 [14] .…”
Section: Sample Sizementioning
confidence: 99%
“…13 However, current treatments for DED have limited e cacy, for this reason, the best way to cope with the disease was taking preventative measures. Our previous studies focus on the effect of screen performance and found that circularly polarized screen and eINK screen can minimize subjective discomfort and ocular surface disorder when reading on smartphones 14,15 . The problem of penetration rate has to be taken into account, so we attempt to nd a simple, convenient and effective prevention strategy.…”
Section: Introductionmentioning
confidence: 99%